Health numeracy and health literacy within the context of management of patients with human immunodeficiency virus - Gakumo CA; Vance DE; Moneyham LD; Deupree JP; Estrada CA (Dove Medical Press, 2013)
C Ann Gakumo,1 David E Vance,1,2 Linda D Moneyham,1 Joy P Deupree,1 Carlos A Estrada3,4 1School of Nursing, 2Center for Nursing Research, 3Veterans Affairs National Quality Scholars Program at the Birmingham Veterans Affairs Medical Center, 4School of Medicine, University of Alabama at Birmingham, Birmingham, AL, USA Abstract: Health literacy, although an important topic in human immunodeficiency virus (HIV), often eclipses health numeracy, which may be equally important for those living with this disease. Health numeracy is the knowledge and application of numerical concepts in health decisions. In our synthesis of the literature, the emerging concept of health numeracy in relation to HIV disease management is reviewed within the context of health literacy. Specifically, we examine health literacy and numeracy by gender, race, education, and age group. From this synthesis, we identify practical implications of health numeracy related to HIV. Keywords: health literacy, health numeracy, human immunodeficiency virus, acquired immune deficiency syndrome, medication adherence